Model of Health and Mouth Health Care Services among Stroke Patients - Wanda Nur Aida; Supriyana Supriyana; Rasipin Rasipin; Bedjo Santoso; Peni Yuliawati (Alta Dharma Publisher, 2020)
Stroke is the main trigger that can cause disability in adults. Stroke patients are known to be vulnerable to oral health problems, such as periodontal disease, due to limitations in their daily activities so that dental and oral hygiene management is neglected. These dental and oral health problems can become worse when patients are treated in a stroke unit. For this reason, dental and oral health care needs to be taken in stroke patients. The study aimed to develop a model of dental and oral health care among stroke patients. Research and Development (R&D), on five research stages, namely: information gathering, product/model design, expert validation and revision, product/model trials (using quasi-experiments with pretest and posttest with control group design). The sample was divided into two groups, the dental and oral health care model in stroke patients in the intervention group and the oral health care model No.284 year 2006 in the control group. Data were tested using normality, paired t-test, post hoc LSD, Mann Whitney, and linear regression. The model of dental and oral health care in stroke patients was relevant as dental and oral health care was shown to be p <0.001. The application of dental and oral health care models in stroke patients effectively improves the skills of gargling in moderate stroke patients p <0.001, increasing the ability to brush teeth in moderate stroke patients p <0.001. The application of dental and oral health care models in stroke patients is useful as an increase in the skills to rinse and brush teeth in moderate stroke patients